2021
DOI: 10.3390/molecules26164991
|View full text |Cite
|
Sign up to set email alerts
|

Subcritical Extracts from Major Species of Oil-Bearing Roses—A Comparative Chemical Profiling

Abstract: A comprehensive chemical profiling of 1,1,1,2-tetrafluoroethane (freon R134a) subcritical extracts from the main genotypes of oil-bearing roses, was performed by gas chromatography–mass spectrometry (GC/MS) and gas chromatography with flame ionization detection (GC-FID) in order to reveal the differences in their chemical composition. One hundred and three individual compounds were identified using GC/MS and their quantitative content was determined using GC-FID, representing 89.8, 92.5, 89.7 and 93.7% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
4
1
Order By: Relevance
“…It might be suggested that the rose oxide odor increases in high altitudes and arid conditions. This amount is much higher than those reported by Bulagrian rose petals [ 12 ], but less than Indian [ 10 ] and Chinese [ 19 ]. Mohsen et al [ 17 ] also reported a similar range for rose oxide in Egyptian rose petals.…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…It might be suggested that the rose oxide odor increases in high altitudes and arid conditions. This amount is much higher than those reported by Bulagrian rose petals [ 12 ], but less than Indian [ 10 ] and Chinese [ 19 ]. Mohsen et al [ 17 ] also reported a similar range for rose oxide in Egyptian rose petals.…”
Section: Resultscontrasting
confidence: 57%
“…The essential oil yield and components of rose oil are attributed to different environmental and genetic factors. Most of the previous research has been reported on the essential oil variation of R. damascena in different countries including India [ 11 ], Bulgaria [ 12 , 13 ], Iran [ 14 ], and Pakistan [ 15 ]. In most of these studies, the oils were analyzed by GC/MS instruments.…”
Section: Introductionmentioning
confidence: 99%
“…The GC-MS analysis uncovered a heterogeneous chemical composition encompassing various classes of volatile compounds, which has been meticulously documented and organized in Table 1 and Table 2 . Considering the paucity of scholarly investigations on the phytochemical composition of R. beggeriana , the GC-MS data were juxtaposed with data obtained from other species belonging to the Rosa genus, as cited in [ 49 , 50 , 51 , 52 ]. The comparative analysis of compositions, specifically the leaves and fruits, revealed a higher degree of complexity in the composition of the latter.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages and limitations of using HFC-134a as a solvent compared to other methods have been discussed [ 24 ]. The potential of using HFC-134a as a solvent was summarized in the study of rose extracts with various chemical compounds [ 25 ] that could be applied to jasmine oil extraction.…”
Section: Introductionmentioning
confidence: 99%